Proposal for a new prognostic score for linac-based radiosurgery in cerebral arteriovenous malformations - Milker-Zabel, Stefanie; Kopp-Schneider, Annette; Wiesbauer, Hannah Judith Stefanie; Schlegel, Wolfgang; Huber, Peter E.; Debus, Jürgen; Zabel-du Bois, Angelika (International journal of radiation oncology, biology, physics, 2012)
Purpose: We evaluate patient-, angioma-, and treatment-specific factors for successful obliteration of cerebral arteriovenous malformations (AVM) to develop a new appropriate score to predict patient outcome after linac-based radiosurgery (RS). Methods and Materials: This analysis in based on 293 patients with cerebral AVM. Mean age at treatment was 38.8 years (4-73 years). AVM classification according Spetzler-Martin was 55 patients Grade I (20.5%), 114 Grade II (42.5%), 79 Grade III (29.5%), 19 Grade IV (7.1%), and 1 Grade V (0.4%). Median maximum AVM diameter was 3.0 cm (range, 0.3-10 cm). Median dose prescribed to the 80% isodose was 18 Gy (range, 12-22 Gy). Eighty-five patients (29.1%) had prior partial embolization; 141 patients (51.9%) experienced intracranial hemorrhage before RS. Median follow-up was 4.2 years. Results: Age at treatment, maximum diameter, nidus volume, and applied dose were significant factors for successful obliteration. Under presumption of proportional hazard in the dose range between 12 and 22 Gy/80% isodose, an increase of obliteration rate of approximately 25% per Gy was seen. On the basis of multivariate analysis, a prediction score was calculated including AVM maximum diameter and age at treatment. The prediction error up to the time point 8 years was 0.173 for the Heidelberg score compared with the Kaplan-Meier value of 0.192. An increase of the score of 1 point results in a decrease of obliteration chance by a factor of 0.447. Conclusion: The proposed score is linac-based radiosurgery-specific and easy to handle to predict patient outcome. Further validation on an independent patient cohort is necessary.
Online 24 October 2011
Gesehen am 29.11.2018